KARAKTERISASI MORFOLOGI SUMBER BENIH TEGAKAN PINUS TERIDENTIFIKASI DI HUTAN PENDIDIKAN UNIVERSITAS HASANUDDIN - Muh. Restu; Gusmiaty Gusmiaty (Biocelebes, 2015)
This study aims  to investigate genetic diversity of identified pine stands at Unhas Extention Forest based on morphological markers.  The methods used are observation and measurement of the variables leaves, stems and plant height.  An analysis of data used the NTSYSpc program (Numerical Taxonomy and Multivariate System) version 2.0.The results showed that there are some morphological similarities such as  the shape of the leaves (needles), the shape of the curve of the leaf tip (tapered), the shape of the curve of the leaf base(tapering), the shape of the leaf margins (flat), the color of top surface of the leaf (dark green), the color of lower surface of leaf (dark green), the state of the upper surface of the leaf (smooth), the state of the lower leaf surface (rough), bark texture (grooved), rod shape (square), and the shape of the canopy (cones) while the other variables showed a difference. The genetic diversity of individual spine based on morphological observations is low.   Keywords  :  Morfological, Genetics,  Diversity, Pine